Flow modeling of actual human nasal cavity for various breathing conditions - Mokhtar, Nur Hazwani (2012)
Flow in the human nasal cavity varies when the body is under various physical activities. However, in order to visualize the flow pattern, traditional in-vivo technique may disturb the flow patterns. In this study, computational method was used to model the flow in the nasal cavity under various breathing conditions. Image from CT-Scan was used to mimic the actual cavity geometry. The image was computationally constructed and EFD. Lab was used to predict the flow behavior. Steady incompressible flow was considered for all case studies. The result shows that, for all breathing conditions, vortices were observed in the turbinate region which confirms the turbinate functions as a filter before the flow reaches the olfactory area. Larger vortices were detected when the flow rates were higher. In the olfactory region, the flow velocities were shown to be dramatically dropped to the ideal odorant uptake velocity range for all cases studied. This study had successfully produced visual description of air flow pattern in the nasal cavity.